Relationships among soil factors and greenhouse gas emissions from furrow-irrigated Rice in the mid-southern, USA - Della Lunga, Diego; Brye, Kristofor R.; Slayden, Jordan M.; Henry, Christopher G.; Wood, Lisa S. (Geoderma Regional, 2021)
The furrow-irrigated rice (Oryza sativa) production system has been developed as an alternative water conservation practice, but results in spatially variable soil conditions. No research has been conducted to relate greenhouse gas (GHG) production to soil and plant properties or environmental factors under furrow-irrigated rice in the mid-southern, USA. The objective of this field study was to evaluate relationships between methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2) fluxes and emissions and global warming potential (GWP) and early season soil properties and environmental factors over two growing seasons (2018 and 2019) under furrow-irrigated rice on a silt-loam soil (Typic Albaqualf). Gas samples were collected weekly between planting and harvest from enclosed-headspace, static chambers and analyzed by gas chromatography. Methane fluxes were correlated with soil moisture (r = 0.18) and oxidation-reduction (redox) potential (r = −0.59), N2O fluxes were correlated with redox potential (r = 0.13), and CO2 fluxes were correlated with soil moisture (r = 0.29), redox potential (r = −0.27), and temperature (r = 0.09). Results suggested that environmental parameters like soil temperature, soil moisture, and redox potential can be included in management practices as controlling factors for production and release of GHG fluxes. Methane, and N2O, emissions were positively (0.36 < r < 0.78) and negatively (−0.33 < r < −0.54) correlated with numerous soil and plant properties. Significant multiple regression models predicting season-long CH4-C, N2O–N, CO2-C, and GWP from a suite of soil and plant properties were identified (0.49 < R2 < 0.78). Results demonstrated that numerous soil, plant, and environmental factors substantially control GHG production and release. •CH4, N2O, and CO2 were simultaneously measured over two rice growing seasons.•CH4 emissions were correlated with EC, P, K, S, Fe, and Zn concentrations.•N2O emissions were correlated with silt, sand, pH, P, Fe, Ca, and Mn concentrations.•Global warming potential was correlated with pH, P, K, Zn, Mg, Na, Mn, and Ca•CO2 emissions were correlated with pH, Ca, Mg, Na, Fe, and Mn concentrations.